2019
DOI: 10.1371/journal.pone.0223109
|View full text |Cite
|
Sign up to set email alerts
|

Sign and goal tracker rats process differently the incentive salience of a conditioned stimulus

Abstract: Sign and goal tracker animals show different behavioral patterns in response to conditioned stimuli, which may be driven by different neural circuits involved in processing stimuli. Here, we explored whether sign and goal-tracker profiles implicated different brain regions and responses to incentive salience of stimuli. We performed three experiments using male Wistar rats. Experiment 1 showed that lesioning the medial prefrontal cortex increased the prevalence of the goal-tracker phenotype. Experiment 2 asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…autoshaping, learning, reward the mPFC (Batten et al, 2018;Tomie et al, 2014), and lesions of the mPFC reduce cue approach behavior (Serrano-Barroso et al, 2019), there is little evidence that the mPFC encodes such Pavlovian cues.…”
Section: Introductionmentioning
confidence: 99%
“…autoshaping, learning, reward the mPFC (Batten et al, 2018;Tomie et al, 2014), and lesions of the mPFC reduce cue approach behavior (Serrano-Barroso et al, 2019), there is little evidence that the mPFC encodes such Pavlovian cues.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, nucleus accumbens shows higher levels of dopamine release in the presence of a CS [142]. Besides, D2 dopamine receptors stimulation reduces ST behavior selectively, in a similar way to medial prefrontal cortex lesion [140,141]. Thus, this model integrates information at different level from this animal model that cover biochemical, anatomical and behavioral level.…”
Section: Starting the Route From Animal Modelsmentioning
confidence: 89%
“…Using the same paradigm, Serrano et al [141] found processing differences of a CS in latent inhibition (LI), other easily quantifiable procedure. LI is a learning process associated to selective attention assessment.…”
Section: Starting the Route From Animal Modelsmentioning
confidence: 99%
“…Taken as a whole, we propose that levels of attention and behavioural measures could help us characterise our participants in different populations. Studies carried out by our research group have shown a clear correlation between attention deficit and levels of impulsivity in an animal model [ 39 ]. These endophenotypes are based in different cue processing, predict vulnerability to behavioural disorders [ 40 ], and could work as a model to evaluate individual differences regarding impulsivity and attention factors [ 7 ].…”
Section: Discussionmentioning
confidence: 99%